Is Job Stability in the United States Falling? Reconciling Trends in the Current Population Survey and Panel Study of Income Dynamics - Jaeger, David A.; Stevens, Ann Huff (Journal of Labor Economics, 1999)
This article considers whether two commonly used sources of information on employer tenure, the Panel Study of Income Dynamics and the Current Population Survey, yield systematically different trends in employer tenure. Little evidence of a discrepancy between the data sets in the 1980s or 1990s is found when comparable samples, variable definitions, and time frames are used. Neither data set shows a significant trend in the share of workers with 1 year or less of tenure, while both data sets show an increase in the fraction of men with less than 10 years of tenure starting in the late 1980s.